CAPITALIZATION OF INDUSTRIAL WASTES IN ECONOMIC CIRCUIT – A WAY TO REDUCTION THE IMPACT UPON ENVIRONMENT DUE TO ITS STORAGE - Luminita Georgeta POPESCU; Florin GROFU (Fiabilitate şi Durabilitate, 2018)
In our country are generated millions of tons of industrial wastes annually. These wastes are stored in industrial wastes deposits which occupied the large surface of soil and also affected the environmental quality, specially the quality of groundwater and surface water. The research activity develop up now, has demonstrated the possibility that these wastes to become the alternative source of raw material for building material industry, based on physical and chemical characteristics similarities with traditional raw material. The paper presents the results of research activities regarding to the use of bottom as raw material in the manufacture of building materials. The use of bottom ash in building material industry is the best way to reduce the huge amounts of this waste that is storage in the historical deposit of thermal power plant. The paper presents the ash deposit of thermal power plant impact upon the environment and some possibilities of ash capitalization in order to reduce of its impact.